A Gricean Interpretation of Nāgārjuna's Catuṣkoṭi and the No-Thesis View. Issue 3 (2nd July 2020) - Hung, Jenny
Abstract : Nāgārjuna (c. 150–250 CE), the famous founder of the Madhyamika School, proposed the positive catuṣkoṭi in his seminal work, Mūlamadhyamakakārikā : 'All is real, or all is unreal, all is both real and unreal, all is neither unreal nor real; this is the graded teaching of the Buddha'. He also proposed the negative catuṣkoṭi : '"It is empty" is not to be said, nor "It is non-empty, " nor that it is both, nor that it is neither; ["empty"] is said only for the sake of instruction' and the no-thesis view: 'No dharma whatsoever was ever taught by the Buddha to anyone'. In this essay, I adopt Gricean pragmatics to explain the positive and negative catuṣkoṭi and the no-thesis view proposed by Nāgārjuna in a way that does not violate classical logic. For Nāgārjuna, all statements are false as long as the hearer understands them within a reified conceptual scheme, according to which (a) substance is a basic categorical concept; (b) substances have svabhāva, and (c) names and sentences have svabhāva .